Effects of season and sex on the concentrations of fecal glucocorticoid metabolites in captive and free-ranging endangered mountain gazelles (Gazella gazella) - Karaer, Mina Cansu; Kankılıç, Tolga; Tavşanoğlu, Çağatay; Cotman, Marko; Čebulj-Kadunc, Nina; Dovč, Alenka; Snoj, Tomaž (Frontiers in Veterinary Science, 2024)
The aim of our study was to measure fecal glucocorticoid metabolite (FGM) concentrations in captive and free-ranging male and female mountain gazelles (Gazella gazella) during their circannual cycle. In addition, FGM concentrations were used to track the intensity of the adrenocortical response in mountain gazelles during the same period. Fecal samples were collected from the ground in the Hatay Mountain Gazelle Wildlife Development Area in the Hatay Province of Türkiye (36°32' N, 36°32' E) in each season of the year (December, April, July, September). The sex of the animals was determined by detecting the SRY gene of the Y chromosome in DNA isolated from the fecal samples. FGM was extracted from dried fecal samples with methanol, and its concentration was measured using a previously partially validated ELISA. The results indicate that season is the most important factor explaining the variability in FGM concentrations in mountain gazelles. In animals of both sexes, the highest concentrations of FGM were observed in September. The values were significantly higher in the captive population, perhaps due to unpredictable stress. In July, FGM concentrations were low in both populations. As a result of the overall analysis across seasons, the comparison of FGM concentrations between captive and free-ranging animals revealed higher concentrations in captive animals only in September but not in other seasons, although higher concentrations have been previously reported for several wild captive species. Due to predation risk, the presence of offspring can be considered a critical point in the biological cycle for the welfare of free-ranging mountain gazelles, as suggested by the higher FGM concentrations in the free-ranging population in July. The high number of visitors could be a challenge for mountain gazelles in captivity, as indicated by higher FGM concentrations during September. Sex had no effect on the FGM concentrations of either population.